2003
DOI: 10.1037/0021-9010.88.2.246
|View full text |Cite
|
Sign up to set email alerts
|

The two faces of transformational leadership: Empowerment and dependency.

Abstract: Followers' identification with the leader and the organizational unit, dependence on the leader, and empowerment by the leader are often attributed to transformational leadership in organizations. However, these hypothesized outcomes have received very little attention in empirical studies. Using a sample of 888 bank employees working under 76 branch manages, the authors tested the relationships between transformational leadership and these outcomes. They found that transformational leadership was positively r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

79
1,070
4
28

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,070 publications
(1,223 citation statements)
references
References 36 publications
79
1,070
4
28
Order By: Relevance
“…As demonstrated by the present study, increased organizational identity in turn generates positive attitudes towards work. This finding supports the results of Shamir et al (1993) and Kark et al (2003) regarding the motivational effect of the transformational leadership style. The present study contributes to what is at present a limited amount of literature on the effect of organizational identification on work engagement and its mediation in the relationship between transformational leaders and the engagement of their followers.…”
Section: Test Of the Structural Modelsupporting
confidence: 81%
See 1 more Smart Citation
“…As demonstrated by the present study, increased organizational identity in turn generates positive attitudes towards work. This finding supports the results of Shamir et al (1993) and Kark et al (2003) regarding the motivational effect of the transformational leadership style. The present study contributes to what is at present a limited amount of literature on the effect of organizational identification on work engagement and its mediation in the relationship between transformational leaders and the engagement of their followers.…”
Section: Test Of the Structural Modelsupporting
confidence: 81%
“…As a result of their increased collective identity, employees are more likely to be engaged in achieving the mission and goals of the organization rather than their own individual interests (Kark, Shamir, & Chen, 2003). Previous studies have also reported that transformational leaders are able to increase the sense of organizational identification of their followers, which in turn has an effect on their work-related attitudes (Shamir et al, 1993;Kark et al, 2003). When employees' organizational identification is enhanced, their perceptions of the organization are expected to be more positive.…”
Section: Transformational Leadership Job Autonomy and Organizationalmentioning
confidence: 99%
“…Walumbwa et al, 2008), and identification with the leader (e.g. Kark et al, 2003). We further emphasize their implications in the next sections.…”
Section: The Role Of Psychosocial Processesmentioning
confidence: 99%
“…Bono & Judge, 2003;Kark et al, 2003;Piccolo & Colquitt, 2006;Walumbwa, Avolio, & Zhu, 2008), highlighting some psychosocial phenomena that seem to be implicated. However, given the number of questions still unanswered, knowledge about the relationships that operate within leadership processes continued to be called for in recent reviews of scholarly studies (Gardner et al, 2010).…”
Section: Transformational Leadership and Follower Performancementioning
confidence: 99%
See 1 more Smart Citation